Robust event‐based control of nonlinear time‐delay systems with partial state feedback. Issue 2 (17th June 2020) - Guo, Jingjing; Zhang, Pengpeng; Liu, Tengfei; Jiang, Zhong‐Ping
Abstract : This article studies the event‐triggered stabilization problem for a class of nonlinear systems subject to time delays and external disturbances. A new event trigger is developed by introducing an auxiliary variable to estimate the influence of external disturbances, time delays and the unmeasured states, such that infinitely fast sampling is avoided. The time‐delay version of the nonlinear small‐gain theorem is employed to guarantee the stability of the closed‐loop event‐triggered system. The new design is applied to solving the event‐triggered output‐feedback control problem for a class of nonlinear uncertain systems in the output‐feedback form.